2011
DOI: 10.1002/uog.7681
|View full text |Cite
|
Sign up to set email alerts
|

Association between different morphological types and abnormal karyotypes in early pregnancy loss

Abstract: Objectives To identify the abnormal transvaginal ultrasound (TVS) findings typical of aneuploidic pregnancies that end with early pregnancy loss (EPL). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 36 publications
(60 reference statements)
10
45
2
Order By: Relevance
“…We found that this condition was correlated with the highest risk of chromosomal abnormalities, which is consistent with the results of a study by Angiolucci et al [18] (Table 3). However, the rate of chromosomal abnormalities in the early symmetrical arrested growth group in our study was much lower than that reported in this previous study (57.7 vs. 100 %).…”
Section: Ultrasound Findingssupporting
confidence: 93%
See 4 more Smart Citations
“…We found that this condition was correlated with the highest risk of chromosomal abnormalities, which is consistent with the results of a study by Angiolucci et al [18] (Table 3). However, the rate of chromosomal abnormalities in the early symmetrical arrested growth group in our study was much lower than that reported in this previous study (57.7 vs. 100 %).…”
Section: Ultrasound Findingssupporting
confidence: 93%
“…Previous studies have shown different results for the correlation between a small embryonic pole and abnormal karyotypes [17,18] (Table 3). In this study, the abnormality rate in the small embryonic pole group was similar to that of the other groups, including the group with normal ultrasound findings, which is inconsistent with the results of Angiolucci et al [18].…”
Section: Ultrasound Findingsmentioning
confidence: 85%
See 3 more Smart Citations